Animal Characteristics and Their Roles in Selected Comparative Slavic Phrasemes - Koletnik, Mihaela; Kaloh Vid, Natalia (Slavistična prepletanja 6, 2025)
This article is a comparative analysis of phrasemes in Standard Slovenian, Croatian, Macedonian and Russian. The phrasemes under investigation all contain a zoonymic element referring to people's emotions, feelings, behavioural patterns, as well as human conditions in terms of their personal, mental and physical characteristics. Animal phrasemes mapping the external appearance of animals and their established, real, supposed and often anthropomorphically ascribed characteristics onto a person are used to describe humans, revealing their characters. At the same time, they are indicative of the value and the position that people in a given community attribute to a particular animal. Animals are in most cases instrumentalized for the purpose of expressing negative human characteristics and interpersonal relationships such as lying, laziness, curiosity, stupidity, anger, hatred, jealousy, drunkenness, nervousness. Less frequently, they may express positive traits such as hard work, strength, loyalty, love and understanding. The animal phrasemes discussed in this article point very clearly to the hierarchical relationship between humans and animals. While the humans remain the centre of the universe, the animals are marginalized and in a subordinate position. Such representation then is necessarily anthropocentric in nature.